Comparative analysis of Mycobacterium tuberculosis pe and ppe genes reveals high sequence variation and an apparent absence of selective constraints. - Christopher R E McEvoy; Ruben Cloete; Borna Müller; Anita C Schürch; Paul D van Helden; Sebastien Gagneux; Robin M Warren; Nicolaas C Gey van Pittius (PLoS ONE, 2012)
Mycobacterium tuberculosis complex (MTBC) genomes contain 2 large gene families termed pe and ppe. The function of pe/ppe proteins remains enigmatic but studies suggest that they are secreted or cell surface associated and are involved in bacterial virulence. Previous studies have also shown that some pe/ppe genes are polymorphic, a finding that suggests involvement in antigenic variation. Using comparative sequence analysis of 18 publicly available MTBC whole genome sequences, we have performed alignments of 33 pe (excluding pe_pgrs) and 66 ppe genes in order to detect the frequency and nature of genetic variation. This work has been supplemented by whole gene sequencing of 14 pe/ppe (including 5 pe_pgrs) genes in a cohort of 40 diverse and well defined clinical isolates covering all the main lineages of the M. tuberculosis phylogenetic tree. We show that nsSNP's in pe (excluding pgrs) and ppe genes are 3.0 and 3.3 times higher than in non-pe/ppe genes respectively and that numerous other mutation types are also present at a high frequency. It has previously been shown that non-pe/ppe M. tuberculosis genes display a remarkably low level of purifying selection. Here, we also show that compared to these genes those of the pe/ppe families show a further reduction of selection pressure that suggests neutral evolution. This is inconsistent with the positive selection pressure of "classical" antigenic variation. Finally, by analyzing such a large number of genes we were able to detect large differences in mutation type and frequency between both individual genes and gene sub-families. The high variation rates and absence of selective constraints provides valuable insights into potential pe/ppe function. Since pe/ppe proteins are highly antigenic and have been studied as potential vaccine components these results should also prove informative for aspects of M. tuberculosis vaccine design.